Increase The Productivity of Financial Advisors' Work Through Persuasive Communication - Flora Grace Putrianti; Sri Muliati Abdullah (Psikostudia : Jurnal Psikologi, 2022)
This study aims to determine the effect of persuasive communication training to increase work productivity in Financial Advisors at Koperasi X. The hypothesis of this research is that the work productivity of Financial Advisors after participating in persuasive communication training increases than the work productivity of Financial Advisors before participating in persuasive communication training. This research is an experimental study using a pretest-posttest only one grup design. The number of subjects in the sample of this research were 14 people in the experimental group. The methods of data collection using data on the ratio of work productivity of Cooperative X. The data analysis technique used the Wilcoxon statistical technique. The results of the analysis of both obtained Z value = -3.297 with p value = 0.001 (p<0.05). This means that there is an increase in work productivity in the research subject between before and after persuasive communication training. Subjects after being given training have a higher work productivity score than before given training. Penelitian ini bertujuan untuk mengetahui pengaruh pelatihan komunikasi persuasif untuk meningkatkan produktivitas kerja pada Financial Advisor di Koperasi X. Hipotesis penelitian ini adalah produktivitas kerja Financial Advisor setelah mengikuti pelatihan komunikasi persuasif meningkat daripada produktivitas kerja Financial Advisor sebelum mengikuti pelatihan komunikasi persuasif. Penelitian ini merupakan penelitian eksperimen dengan menggunakan pretest-posttest only one grup design. Jumlah subjek pada sampel penelitian ini adalah sebanyak 14 orang kelompok eksperimen. Metode pengumpulan data menggunakan data rasio produktivitas kerja Koperasi X. Teknik analisis data menggunakan teknik statistik Wilcoxon. Hasil analisis keduanya diperoleh nilai Z = -3,297 dengan nilai p = 0,001 (p<0,05). Hal ini berarti ada peningkatan produktivitas kerja pada subjek penelitian antara sebelum dan sesudah pelatihan komunikasi persuasif. Subjek sesudah diberi pelatihan memiliki skor produktivitas kerja lebih tinggi daripada sebelum diberi pelatihan.